2017
DOI: 10.1103/physrevapplied.8.064013
|View full text |Cite
|
Sign up to set email alerts
|

Free-Space Quantum Communication with a Portable Quantum Memory

Abstract: The realization of an elementary quantum network that is intrinsically secure and operates over long distances requires the interconnection of several quantum modules performing different tasks. In this work we report the interconnection of four different quantum modules: (i) a random polarization qubit generator, (ii) a free-space quantum communication channel, (iii) an ultra-low noise portable quantum memory and (iv) a qubit decoder, in a functional elementary quantum network possessing all capabilities need… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Recent studies have demonstrated the potential of room-temperature quantum devices for this purpose, including the demonstration of noiseless room-temperature quantum memories for single-photons and polarization qubits [23][24][25] with coherence times of several seconds in ambient conditions [26]. Furthermore, preliminary quantum networks using room-temperature memories are already available [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the potential of room-temperature quantum devices for this purpose, including the demonstration of noiseless room-temperature quantum memories for single-photons and polarization qubits [23][24][25] with coherence times of several seconds in ambient conditions [26]. Furthermore, preliminary quantum networks using room-temperature memories are already available [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The latter avenue has given rise to the field of quantum optics, which is now widely studied theoretically and employed experimentally [4]. Development of quantum optics has led to the formation of the rapidly growing area of quantum optical technologies, with applications such as quantum sensing [5][6][7], quantum computing [8], and quantum communication with conventional [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and small satellites [24,25]. These applications have in common the fact that, in order to surpass their classical counterparts, a tremendous control over quantum states is required.…”
Section: Introductionmentioning
confidence: 99%
“…It is also somewhat surprising that even though only a small fraction of atoms traverse both laser beams, their contribution to the resonance slope is comparable with the single-channel resonance amplitude. Moreover, the possibility of such spin coherence transfer may need to be accounted for in multiplexed experimental arrangements, commonly used in quantum optics [20][21][22].…”
Section: Introductionmentioning
confidence: 99%